Radiation Therapy for Liver Tumors : Fundamentals and Clinical Practice - Meyer, Jeffrey; Schefter, Tracey (Springer International Publishing : Imprint: Springer, 2017)
The management of liver tumors is a nexus of interactions among multiple medical specialties, including radiation oncology. A multitude of liver-directed therapies are available for patients, ranging from surgery and liver transplantation to intra-arterial therapies, thermal ablation procedures, systemic therapies, and radiation treatments. With the introduction of hypofractionated irradiation, particle therapy, and radioembolization, there is growing interest in the use of radiation as a treatment for liver malignancies. This book examines basic principles of the management of liver tumors. The evolving roles of x-ray and particle therapies as well as radioembolization in the treatment of liver tumors is the main focus. A theme of multidisciplinary management is also emphasized, as surgical, interventional and systemic therapies are reviewed. A unique resource that discusses the role of radiation treatment in the context of other liver-directed therapies, Radiation Therapy for Liver Tumors is of broad interest to radiation oncologists, surgeons, hepatologists, medical oncologists, and radiologists.
Keywords: Medicine.; Radiotherapy.; Oncology.; Abdominal surgery.; elektronické knihy; electronic books